2019
DOI: 10.3390/ijms20020293
|View full text |Cite
|
Sign up to set email alerts
|

miRNA Polymorphisms and Risk of Cardio-Cerebrovascular Diseases: A Systematic Review and Meta-Analysis

Abstract: Recently extensive focus has been concentrated on the role of miRNAs in the initiation and progression of cardio-cerebrovascular diseases (CCDs) which constitute a range of conditions including cardiovascular diseases (CVDs, especially coronary artery disease (CAD)), congenital heart disease (CHD) and cerebrovascular diseases (CBVDs, especially the ischemic stroke (IS)). An increasing number of studies are evaluating the association between different miRNA polymorphisms and risk of CCDs, but results have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 83 publications
0
31
0
Order By: Relevance
“…Several studies have reported the association between miR-14a and CAD; the results of a recent systematic review and meta-analysis supported the existence of a role for miR-146a rs2910164 polymorphism in determining the susceptibility to cardio-cerebrovascular diseases, especially CAD (26).…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have reported the association between miR-14a and CAD; the results of a recent systematic review and meta-analysis supported the existence of a role for miR-146a rs2910164 polymorphism in determining the susceptibility to cardio-cerebrovascular diseases, especially CAD (26).…”
Section: Discussionmentioning
confidence: 95%
“…Rs2910164 substitutes a C nucleotide in the 3′ arm of hsa-miR-146a precursor (MI0000477) with a G nucleotide [97]. This substitution induces a mispairing in the precursor structure and it affects the third base of the seed region of hsa-miR-146a-3p (MIMAT0004608).…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence suggests that rs2910164 might influence the maturation and expression of miR-146a in a context dependent paradigm, in which the true effect of either allele might depend on the cell type and the disease status [97]. Observations that support this paradigm include the discrepancies between pathological and normal samples in terms of miR-146a genotype-expression correlation [98,99] and opposite effects of rs2910164 alleles on miR-146a expression in different cell types or diseases [97,98,99,100,101]. Moreover, miRNA-mediated regulation of gene expression has been shown to be highly influenced by cell-type specific conditions [102].…”
Section: Resultsmentioning
confidence: 99%
“…It is now clear that dysregulated expression of miRNAs can exert profound effects on cells function and, as a result, leads to various pathological and occasionally malignant outcomes [54][55][56][57]. The involvement of miRNAs was showed in more than 70 different diseases such as cancer, viral infection, gastrointestinal malignancies, diabetes, immune-related diseases, and neurodegenerative disorders [51,53,[58][59][60][61][62][63][64]. In view of this, miRNAs are considered an interesting target for therapeutic intervention; to date, approximately 20 miRNA-and siRNA-based therapeutics are currently in the preclinical and/or in clinical trials [45,47].…”
Section: Clinical Applications Of Mirnasmentioning
confidence: 99%